Labor-intensive firms are a catalyst for monetary policy and its distributive effects - Jan Philipp Fritsche (DIW Weekly Report, 2021)
The mandate of the European Central Bank's monetary policy is to ensure price stability. Interest rate changes by the ECB affect labor costs and the value added of firms. If both dimensions are not equally affected, monetary policy has a distributive effect between workers and shareholders. Balance sheet data from over two million companies in the euro area show that the labor costs in labor-intensive companies decrease more strongly than in other firms in response to interest rate increases. Heterogeneity of the companies can lead to asymmetries in the transmission of monetary policy in the euro area countries. Therefore, new monetary policy instruments targeting firms should be discussed. European labor markets with uniform labor law and European labor market institutions, along with the long-discussed banking and capital markets union, could help monetary policy affect the whole euro area more evenly.
Keywords: D22; D31; E23; E32; C52; 330; Monetary policy; firm heterogeneity; labor share; financial frictions; DSGE model validation